Espacio y opresión en el teatro de Patricia Zangaro - Persino, María Silvina (Latin American Theatre Review, 2006)
Patricia Zangaro is part of a new generation of Argentine playwrights that became very productive during the last decade of the twentieth century. The imaginary world created in her plays is populated by marginalized characters, discriminated against because of their social class, race, age, or sexuality. Their living on the edges of society is not only a metaphor, since they inhabit liminal spaces such as trash dumps, the banks of a polluted stream, or the bordering areas of the desert. With the exception of the most recent play within this corpus, Zangaro does not offer an optimistic view on marginalization. Indeed, most of the characters do not show an awareness of their disenfranchisement that would prompt them to action in order to change their oppressive situation. On the contrary, in some cases we see them acting as oppressors themselves, subjugating others even less fortunate. (MSP, in Spanish)